IMPLEMENTASI PEMBELAJARAN FIQH PADA PRODUK HALAL DI INDUSTRY KECIL MENENGAH (IKM) - Ulah Al Chumairoh Machfud, Nailul; Nabilah, Farida; Ayu Munfaridah, Lely; Kholidatur Rodiyah, Siti (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The purpose of this study was to find out how fiqh learning may be applied to halal goods from small and medium sized bussines (IKM). This is side story sinve a lot of student enterpreneurs are developing due of the influence of their own education. Because of this a more thorough examination of how fiqh learning applies to halal items is necessart to determine whatever or not thet may be considered halal. This stdy employs a qualitative, phenomenologic al approach as its methodology. The findigs of study indicate that small and medium industrial entrepreneurs (IKM) have started to use fiqh knowledge to halal products.